Elections in Bangladesh: signs democracy or tyranny? - Ahsan, Abdullahil (Turkey Agenda, 2015)
Last Tuesday on April 28 Bangladesh has held mayoral elections in two most populated cities of the country. The Election Commission has declared three ruling party Awami League (AL) supported candidates winners in the election while the main opposition party Bangladesh Nationalist Party (BNP) at about 11 am of the Election Day declared its decision to boycott it. This is not the first time that BNP has boycotted elections in Bangladesh. It boycotted the last parliamentary elections which were held in January 2104 and AL won more than half the parliamentary seats uncontested. Earlier AL led coalition came to power following a heavily rigged parliamentary elections held in 2008. In fact, due to the heavy rigging of ballots, BNP decided to boycott the election in 2008. ......